Pengarauh Adversity Quotient dan Dukungan Sosial Terhadap Kesehatan Mental Melalui Pendidikan Agama Kristen Penyintas Bunuh Diri di Kota Manado - Noya, Novri Naftali; Weol, Wolter; Binilang, Benny (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the direct and significant influence of Adversity Quotient (X1) on the mental health of suicide survivors in Manado City (Y), the direct and significant influence of social support (X2) on the mental health of suicide survivors in Manado City (Y), the direct and significant influence of Christian religious education (Z) on the mental health of suicide survivors in Manado City (Y), the direct and significant influence of Adversity Quotient (X1) on Christian religious education (Z), the direct and significant influence of social support (X2) on Christian religious education (Z), the indirect and significant influence of Adversity Quotient (X1) through Christian religious education (Z) on the mental health of suicide survivors in Manado City (Y), and the indirect and significant influence of social support (X2) through Christian religious education (Z) on the mental health of suicide survivors in Manado City (Y). This study uses a quantitative research method. The research sample consists of 45 suicide survivors in Manado City. The analysis technique used is SPSS 29.